Oxidized high‐density lipoprotein accelerates atherosclerosis progression by inducing the imbalance between treg and teff in LDLR knockout mice. Issue 5 (May 2015) - Ru, Ding; Zhiqing, He; Lin, Zhu; Feng, Wu; Feng, Zhang; Jiayou, Zhang; Yusheng, Ren; Min, Fan; Chun, Liang; Zonggui, Wu
Abstract : High density lipoprotein (HDL) dysfunction has been widely reported in clinic, and oxidation of HDL (ox‐HDL) was shown to be one of the most common modifications in vivo and participate in the progression of atherosclerosis. But the behind mechanisms are still elusive. In this study, we firstly analyzed and found strong relationship between serum ox‐HDL levels and risk factors of coronary artery diseases in clinic, then the effects of ox‐HDL in initiation and progression of atherosclerosis in LDLR knockout mice were investigated by infusion of ox‐HDL dissolved in chitosan hydrogel before the formation of lesions in vivo . Several new evidence were shown: (i) the serum levels of ox‐HDL peaked early before the formation of lesions in LDLR mice fed with high fat diet similar to oxidative low density lipoprotein, (ii) the formation of atherosclerotic lesions could be accelerated by infusion of ox‐HDL, (iii) the pro‐atherosclerotic effects of ox‐HDL were accompanied by imbalanced levels of effector and regulatory T cells and relative gene expressions, which implied that imbalance of teff and treg might contribute to the pro‐atherosclerosis effects of ox‐HDL.